Phenotypic identification & molecular detection of bla(ndm-1) gene in multidrug resistant Gram-negative bacilli in a tertiary care centre - Shenoy, K. Anjana (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND & OBJECTIVES: Carbapenemase-producing Enterobacteriaceae isolates have been increasingly identified worldwide. Though molecular data regarding New Delhi metallo-beta-lactamase-1 (NDM-1) producers are available, data regarding their rate of infection in a hospital setting and percentage among different clinical isolates are scarce. Hence, this study was undertaken to determine the occurrence of bla(NDM-1) gene among clinical isolates of multidrug resistant Gram-negative bacilli (MDRGNB) in a tertiary care centre in Bangalore, Karnataka, India. METHODS: A total of 74 MDRGNB isolates were studied. These were screened for MBL production by phenotypic assays such as double disk synergy test (DDST) and Modified Hodge's test (MHT). PCR was performed for the molecular detection of the gene and antibiograms were confirmed by automated bacteriology system. RESULTS: Of the 74 MDRGNB isolates, 34 were positive for bla(NDM-1) gene. All isolates were resistant to aztreonam and two isolates were resistant to tigecycline. Complete resistance to the tested carbapenems was seen in 28 (82.35%) of the positive isolates whereas variable carbapenem resistance was seen in six (17.64%) of the positive clinical isolates. Of the total 34 PCR positive isolates, 33 (97.05%) NDM-1 producers were identified by DDST and 26 (76.47%) by MHT as producers of MBL. INTERPRETATION & CONCLUSIONS: A high percentage of plasmid encoded NDM was noted in MDRGNB. Phenotypic and molecular screening should be employed along with routine antimicrobial susceptibility testing to reflect the true number of metallo-beta-lactamase producers.